Near-zero-waste processing of low-grade, complex primary ores and secondary raw materials in Europe: technology development trends - Spooren, Jeroen; Binnemans, Koen; Björkmalm, Johanna; Breemersch, Koen; Dams, Yoko; Folens, Karel; González-Moya, María; Horckmans, Liesbeth; Komnitsas, Konstantinos; Kurylak, Witold; Lopez, Maria; Mäkinen, Jarno; et al. (Resources, conservation and recycling, 2020)
•Metal recovery from low-grade resources evolves towards near-zero-waste processing.•A novel metallurgical toolbox concept is proposed to process low-grade ores.•Novel process techniques are discussed.•Low-grade ore processing requires new circular economy business models. With an increasing number of low-grade primary ores starting to be cost-effectively mined, we are at the verge of mining a myriad of low-grade primary and secondary mineral materials. At the same time, mining practices and mineral waste recycling are both evolving towards sustainable near-zero-waste processing of low-grade resources within a circular economy that requires a shift in business models, policies and improvements in process technologies. This review discusses the evolution towards low-grade primary ore and secondary raw material mining that will allow for sufficient supply of critical raw materials as well as base metals. Seven low-grade ores, including primary (Greek and Polish laterites) and secondary (fayalitic slags, jarosite and goethite sludges, zinc-rich waste treatment sludge and chromium-rich neutralisation sludge) raw materials are discussed as typical examples for Europe. In order to treat diverse and complex low-grade ores efficiently, the use of a new metallurgical systems toolbox is proposed, which is populated with existing and innovative unit operations: (i) mineral processing, (ii) metal extraction, (iii) metal recovery and (iv) matrix valorisation. Several promising novel techniques are under development for these four unit-operations. From an economical and environmental point of view, such processes must be fitted into new (circular) business models, whereby impacts and costs are divided over the entire value chain. Currently, low-grade secondary raw material processing is only economic and environmentally beneficial when the mineral residues can be valorised and landfill costs are avoided and/or incentives for waste processing can be taken into account.